PERAN GURU DALAM IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA DI SMP RADEN FATAH CIMANGGU KABUPATEN CILACAP - Muhamad Aldi; Suparjo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article discusses a curriculum concept that focuses on developing student potential. P5 Merdeka Curriculum is the Pancasila Student Profile Strengthening Project, a curriculum concept that focuses on developing student potential holistically and centered on students. P5 aims to strengthen student character and develop competencies in accordance with the Pancasila Student Profile. This article aims to determine the implementation of the Pancasila Student Profile Strengthening Project in the schools studied. This article uses library research from various books, articles and research results to obtain the information being studied. The results obtained by the author are the implementation of the Pancasila Student Profile Strengthening Project in one academic year, namely the 2024-2025 academic year in one of the schools in Cilacap Regency, namely Raden Fatah Cimanggu Middle School. Based on the results of the analysis and conclusions in the discussion chapter, the author proposes the following suggestions: teachers must be able to identify the Pancasila Student Profile Strengthening Project, teachers must be able to implement the Pancasila Student Profile Strengthening Project according to the level of education of students, teachers must be able to become facilitators who help students develop their potential and character, especially in the Pancasila Student Profile Strengthening Project that is in accordance with the needs of students and schools.